2014
DOI: 10.1155/2014/684508
|View full text |Cite
|
Sign up to set email alerts
|

Genus Caulophyllum: An Overview of Chemistry and Bioactivity

Abstract: Recently, some promising advances have been achieved in understanding the chemistry, pharmacology, and action mechanisms of constituents from genus Caulophyllum. Despite this, there is to date no systematic review of those of genus Caulophyllum. This review covers naturally occurring alkaloids and saponins and those resulting from synthetic novel taspine derivatives. The paper further discussed several aspects of this genus, including pharmacological properties, mechanisms of action, pharmacokinetics, and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…It is distributed in the northeast Tibet, Hubei provinces of China, native communities of North America, Its root and rhizome have beenused to induce childbirth, ease the pain of labor, rectify delayed or irregular menstruation, alleviate heavy bleeding and pain during menstruation [ 2 ]. Modern pharmacological studies have demonstrated that alkaloids and triterpenoidsaponins are responsible for its major biological function as an anti-inflammatory [ 3 ]. As part of our effort to search for novel triterpene from C. robustum Maxim, we report here the isolation and structure determination of the three new terpenoids: ( 1 ) 23-hydroxy-3,19-dioxo-olean-12-en-28-oic-acid; ( 2 ) 23-hydroxy-3,11-dioxo-olean-12-en-28-oic acid; and ( 3 ) 16 α ,23-dihydroxy-3-oxo-olean-12-en-28-oic acid ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed in the northeast Tibet, Hubei provinces of China, native communities of North America, Its root and rhizome have beenused to induce childbirth, ease the pain of labor, rectify delayed or irregular menstruation, alleviate heavy bleeding and pain during menstruation [ 2 ]. Modern pharmacological studies have demonstrated that alkaloids and triterpenoidsaponins are responsible for its major biological function as an anti-inflammatory [ 3 ]. As part of our effort to search for novel triterpene from C. robustum Maxim, we report here the isolation and structure determination of the three new terpenoids: ( 1 ) 23-hydroxy-3,19-dioxo-olean-12-en-28-oic-acid; ( 2 ) 23-hydroxy-3,11-dioxo-olean-12-en-28-oic acid; and ( 3 ) 16 α ,23-dihydroxy-3-oxo-olean-12-en-28-oic acid ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…C. robustum consists of more than 60 constituents, including sterols, triterpenes, glycosides, and alkaloids. Triterpene saponins are believed to be the major bioactive compounds contributing to the anti-inflammatory effects on RA [ 10 ]. Triterpene saponins constitute an important class of potential pharmacological agents possessing a range of different physiological activities including anticancer, anticoagulation, anti-inflammation, antibacterial, analgesic, and comparative immune-modulation activity [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Historically, C. robustum is a traditional Chinese herb used in the treatment of RA [ 10 ]. It is acrid and bitter in taste and warm in nature.…”
Section: Introductionmentioning
confidence: 99%
“…(21) Magnoflorine, taspine, and boldine, belonging to aporphine alkaloids, are found in Caulophyllum. (22) Typical quinolizidine alkaloids are also present in this genus. Alkaloids with piperidine-acetophenone conjugates, rare in the plant kingdom, are only found in Caulophyllum and Boehmeria.…”
Section: Nandinoideae Subfamilymentioning
confidence: 97%